Konseptual syirkah dalam islam - raminah, raminah (Maliki Interdisciplinary Journal, 2025)
In the context of this existence, many Muslims do not fully understand how to conduct shirkah or partnership in accordance with the principles of sharia. This lack of understanding has resulted in the emergence of shirkah practices that follow Western or European procedures, which are not necessarily in accordance with the teachings of sharia. One of the distinctive features of Islamic law is its ability to provide answers to the legal status of situations faced by its people, including in the case of shirkah. In principle, the complexities associated with contemporary shirkah cannot be separated from the basic principles of shirkah itself, so that it remains in accordance with the principles of sharia and makes it a legitimate business. The principles that must be adhered to in the implementation of shirkah (cooperation) are that the partnership is a transaction that is permitted to be represented; the percentage distribution of profits and losses for each party involved is explained when the agreement is made; profits are obtained from the profits generated by the joint property, not from other sources of wealth..